Perissodactyla (Rhinocerotidae and Equidae) from Kanapoi. Issue 140 (March 2020) - Geraads, Denis
Abstract: The Kanapoi collection of Rhinocerotidae, first studied by Hooijer and Patterson (1972), now consists of 25 specimens and substantial reinterpretation of their affinities is made here. Kanapoi post-dates the extinction of Brachypotherium and the whole collection belongs to the Dicerotini. It is important because it includes the type-specimen of Diceros praecox, a species that remains poorly known, but looks slightly larger and more primitive than the modern 'black' rhino, Diceros bicornis . A second species is probably ancestral to the modern 'white' rhino, Ceratotherium simum ; it looks identical to the Pleistocene North African Ceratotherium mauritanicum, of which Ceratotherium efficax is probably a synonym. The evolution of the Dicerotini in Africa can be regarded as an increasing divergence in diet and related morphofunctional adaptations in the two lineages. The co-occurrence at Kanapoi of both Diceros and Ceratotherium, with distinct dietary preferences, suggests some habitat heterogeneity, although the low sample size prevents robust paleoecological conclusions. The Equidae are also rare and consist mostly of isolated teeth. I take the most parsimonious option of tentatively including all of them in a single species, whose identification is left open. Dental features of eastern African Pliocene to Pleistocene hipparions may reflect increasing adaptation to grazing.